Integrity Development Through PSM For Corruption Prevention Among Public Servant - Syamsir; Ali Embi, Muhamad (International Journal of Psychosocial Rehabilitation, 2020)
-This article discusses the importance of fostering public service motivation (PSM) to build public servants with integrity for the prevention of corruption. Public service motivation is a characteristic of the public servants that should be owned and must exist among them. Public service motivation is often defined as the motivating force that encourages individuals to provide the best public service and meaningful to the community; or motivation that contains an individual service orientation that is intended for the benefit of society, orientation to help others, and passion to obtain intrinsic achievement or achievement-oriented service. Public service motivation among public servants is very important and it should be a serious concern and a main priority in order to realize the integrity public service and will ultimately be able to prevent corruption among public employees (state civil servants).